2009
DOI: 10.1097/qai.0b013e3181acb4ff
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir/Ritonavir Affects Pharmacokinetic Exposure of Artemether/Lumefantrine in HIV-Uninfected Healthy Volunteers

Abstract: Coadministration of artmether/lumefantrine and LPV/r can be carried out for patients coinfected with malaria and HIV. Formal safety analysis of concomitant therapy should be addressed by future studies among individuals living in malaria-endemic regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
73
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 18 publications
6
73
1
Order By: Relevance
“…However, malaria illness could attenuate the autoinduction seen in our clinically well HIV-infected patients and in previously described studies on healthy volunteers. Artemether and dihydroartemisinin exposure in our ART-naïve group is similar to previously published results in healthy volunteer studies (15,21), suggesting that there is not a marked HIV disease effect.…”
Section: Discussionsupporting
confidence: 79%
“…However, malaria illness could attenuate the autoinduction seen in our clinically well HIV-infected patients and in previously described studies on healthy volunteers. Artemether and dihydroartemisinin exposure in our ART-naïve group is similar to previously published results in healthy volunteer studies (15,21), suggesting that there is not a marked HIV disease effect.…”
Section: Discussionsupporting
confidence: 79%
“…The AUCs for ARM and DHA in the present study were similar to those reported previously in adults with malaria (21, 24) but higher than those in healthy adults (14,19,20). Our terminal elimination half-life for ARM was longer than those reported in these studies (16.4 versus 1.5 to 3.9 h), while for DHA, it was shorter (0.80 versus 1.2 to 2.1 h).…”
Section: Discussioncontrasting
confidence: 44%
“…Both ARM and DHA have short half-lives (14, 19-21, 24, 25, 31) but a rapid effect on parasitemia. LUM is a highly lipophilic drug with a longer half-life (11,13,14,19,20,24,30) which is combined with ARM primarily to prevent late recrudescence. Although the pharmacokinetic (PK) properties of ARM, DHA, and LUM in adults have been well documented (4, 5, 11, 13-15, 19-22, 24, 30), there are scant and inconsistent data relating to the disposition of desbutyl-lumefantrine (DBL), a potent LUM metabolite (26,28,29,32) that may influence AL's treatment outcome (32).…”
mentioning
confidence: 99%
“…First, the antimalarial activity of lopinavir, with drug levels boosted by ritonavir, may kill erythrocytic parasites before infections progress to clinical illness. Second, after therapy for a prior infection, inhibition of cytochrome P 450 3A4 by ritonavir may extend exposure to antimalarial drugs, as has been demonstrated for lumefantrine (12), thereby prolonging the period during which a drug circulates at concentrations adequate to prevent new infections. Third, through synergistic effects, cocirculating antimalarials and antiretrovirals may prevent new infections more effectively than the antimalarials alone.…”
Section: Discussionmentioning
confidence: 99%
“…Considering pharmacokinetics, the HIV protease inhibitor ritonavir is widely used to enhance the circulating concentrations of other protease inhibitors, but it may also affect exposure to many other drugs that are metabolized by cytochrome P 450 3A4. Indeed, in normal volunteers, exposure to the antimalarial lumefantrine, a component of the ACT artemether-lumefantrine, was markedly enhanced by coadministration of lopinavirritonavir (12), and exposure to a number of other antimalarial drugs may be affected by ritonavir or other agents (41). Considering antimalarial efficacy, HIV protease inhibitors have been shown to potentiate the activity of chloroquine (14,15,23) and to either augment (29) or antagonize (16) the activity of artemisinins.…”
mentioning
confidence: 99%